Development of an anti-Pseudomonas aeruginosa therapeutic monoclonal antibody WVDC-5244 - Horspool, Alexander M.; Sen-Kilic, Emel; Malkowski, Aaron C.; Breslow, Scott L.; Mateu-Borras, Margalida; Hudson, Matthew S.; Nunley, Mason A.; Elliott, Sean; Ray, Krishanu; Snyder, Greg A.; Miller, Sarah Jo; Kang, Jason; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
The rise of antimicrobial-resistant bacterial infections is a crucial health concern in the 21st century. In particular, antibiotic-resistant Pseudomonas aeruginosa causes difficult-to-treat infections associated with high morbidity and mortality. Unfortunately, the number of effective therapeutic interventions against antimicrobial-resistant P. aeruginosa infections continues to decline. Therefore, discovery and development of alternative treatments are necessary. Here, we present pre-clinical efficacy studies on an anti-P. aeruginosa therapeutic monoclonal antibody. The anti-P. aeruginosa antibody (WVDC-5244) bound P. aeruginosa clinical strains of various serotypes in vitro, even in the presence of alginate exopolysaccharide. In addition, WVDC-5244 induced opsonophagocytic killing of P. aeruginosa in vitro in J774.1 murine macrophage, and complement-mediated killing. In a mouse model of acute pneumonia, prophylactic administration of WVDC-5244 resulted in an improvement of clinical disease manifestations and reduction of P. aeruginosa burden in the respiratory tract compared to the control groups. This study provides promising pre-clinical efficacy data on a new monoclonal antibody with therapeutic potential for P. aeruginosa infections.